Activation of GABABR Attenuates Intestinal Inflammation by Reducing Oxidative Stress through Modulating the TLR4/MyD88/NLRP3 Pathway and Gut Microbiota Abundance - Ziteng Deng; Dan Li; Lu Wang; Jing Lan; Jiaqi Wang; Yunfei Ma (MDPI AG, 2024)
Oxidative stress emerges as a prominent factor in the onset and progression of intestinal inflammation, primarily due to its critical role in damaging cells and tissues. GABAergic signaling is important in the occurrence and development of various intestinal disorders, yet its effect on oxidative stress remains unclear. We attempted to assess whether GABAergic signaling participated in the regulation of oxidative stress during enteritis. The results showed that lipopolysaccharide (LPS) significantly decreased γ-aminobutyric acid (GABA) levels in the ileal tissues of mice. Interestingly, the application of GABA significantly repressed the shedding of intestinal mucosal epithelial cells and inflammatory cell infiltration, inhibited the expressions of proinflammatory factors, including granulocyte colony-stimulating factor and granulocyte-macrophage colony stimulating factor, and enhanced the levels of anti-inflammatory cytokines interleukin (IL)-4 and IL-10, indicating that GABA could alleviate enteritis in mice. This observation was further supported by transcriptome sequencing, revealing a total of 271 differentially expressed genes, which exhibited a marked enrichment of inflammatory and immune-related pathways, alongside a prominent enhancement of GABA B receptor (GABABR) signaling following GABA administration. Effectively, Baclofen pretreatment alleviated intestinal mucosal damage in LPS-induced mice, suppressed proinflammatory cytokines IL-1β, IL-6, and tumor necrosis factor alpha expressions, and boosted total antioxidant capacity, superoxide dismutase (SOD), and glutathione (GSH) levels. Moreover, Baclofen notably enhanced the viability of LPS-stimulated IPEC-J2 cells, contracted the proinflammatory secretion factors, and reinforced SOD, GSH, and catalase levels, emphasizing the anti-inflammatory and antioxidant effects associated with GABABR activation. Mechanistically, Baclofen restrained the mRNA and protein levels of toll-like receptor 4 (TLR4), myeloid differentiation factor 88 (MyD88), nucleotide-binding oligomerization domain, leucine-rich repeat and pyrin domain-containing 3 (NLRP3), and inducible nitric oxide synthase, while elevating nuclear factor erythroid 2-related factor 2 and heme oxygenase-1 in both mice and IPEC-J2 cells, indicating that activating GABABR strengthened antioxidant abilities by interrupting the TLR4/MyD88/NLRP3 pathway. Furthermore, 16S rDNA analysis demonstrated that Baclofen increased the relative abundance of probiotic, particularly Lactobacillus, renowned for its antioxidant properties, while reducing the relative richness of harmful bacteria, predominantly Enterobacteriaceae, suggesting that GABABR signaling may have contributed to reversing intestinal flora imbalances to relieve oxidative stress in LPS-induced mice. Our study identified previously unappreciated roles for GABABR signaling in constricting oxidative stress to attenuate enteritis, thus offering novel insights for the treatment of intestinal inflammation.